Clinical experience in the use of bioactive gel in the treatment of chronic apical periodontitis - S. A. Demyanenko; Yu. V. Tofan (Эндодонтия Today)
Aim. Along with the improvement of methods of medical and instrumental treatment and root canal obturation of great interest are the development and study of the clinical efficacy of drugs zaapikalnogo use aimed at stimulating tissue regeneration in the apical periodontium. Materials and methods. The article presents the results of treatment of chronic apical periodontitis in 78 patients. The total number of cured teeth was 80. In the control group (36 patients) have adopted a comprehensive treatment using written down introduction into the periapical lesion destruction of bone autoplasma patient's blood, enriched with platelets, in combination with a bioactive gel "Collapan-S".Results. It was found that the use of this combination helps to accelerate the processes of repair of bone periodontal tissue and leads to a reduction in the duration of treatment. This is confirmed by the optical density of bone tissue in chronic apical periodontitis using radiovisiography and computed tomography.